2022
DOI: 10.1007/s43546-022-00291-6
|View full text |Cite
|
Sign up to set email alerts
|

Examining the macro-determinants of tourist arrivals in India

Abstract: The present study analyzes the asymmetric association of exchange rate and world income with inbound tourism demand in India using a recently developed nonlinear autoregressive distributed lag model. For this purpose, the study uses monthly data from January 2003 to December 2020 for inbound tourism demand, real effective exchange rate, and world income as the variables of the model. The study used an asymmetric causality test on the lines of Hatemi-J. The findings confirm the existence of a nonlinear associat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 62 publications
0
2
0
Order By: Relevance
“…Second, there is a negative effect of the exchange rate on the number of tourist visits [12], [13], [14]. Third, there is a positive/negative effect of the exchange rate on the number of tourist visits [15], [16], [17], [18] Theoretically, the exchange rate has a positive correlation with tourist visits in a country because the price decreases when it is calculated in foreign currency. As shown by the results of studies by [9], [10], they found a positive and significant effect of the exchange rate on the number of tourist arrivals in Indonesia.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Second, there is a negative effect of the exchange rate on the number of tourist visits [12], [13], [14]. Third, there is a positive/negative effect of the exchange rate on the number of tourist visits [15], [16], [17], [18] Theoretically, the exchange rate has a positive correlation with tourist visits in a country because the price decreases when it is calculated in foreign currency. As shown by the results of studies by [9], [10], they found a positive and significant effect of the exchange rate on the number of tourist arrivals in Indonesia.…”
Section: Introductionmentioning
confidence: 99%
“…Then [18] found a long-term nonlinear relationship between the exchange rate and tourism demand, positive exchange rate shocks have a greater long-term impact on tourist arrivals than negative exchange rate shocks in India. Positive shocks have a short-term significant impact on tourism demand.…”
Section: Introductionmentioning
confidence: 99%